Increasing Organizational Commitment of Gen Z Workers: The Role of Leadership, Employee Engagement, and Work-Life Balance - Revika Hikmah Rahmawati; Sri Padmantyo (Universitas Muhammadiyah Surakarta, 2025)
Purpose: Pandemic covid-19 has changed the world of work by encouraging the implementation of remote working systems and accelerating the use of technology. This has created challenges for adaptation and new dynamics. This study aims to analyze the influence of leadership, employee engagement, and work-life balance on organizational commitment among Gen Z employees.Methodology: This study uses a quantitative method with a non-probability sampling approach through purposive sampling. The data collection process involves distributing questionnaires with a Likert scale to gather information. This study involved 200 respondents who were selected as samples. The data analysis method used is SPSS 25.Results: This study reveals that leadership, employee engagement, and work-life balance have a positive and significant influence on organizational commitment, both partially and simultaneously.Applications/Originality/Value: This study recommends the importance of strengthening the implementation of organizational strategies that focus on strengthening leadership, increasing employee engagement, and supporting work-life balance.